The effects of fin-and-tube evaporator geometry on heat pump performance under dehumidifying conditions - Erdem, Serkan (ELSEVIER SCI LTD, 2015)
A heat pump tumble dryer model was developed to investigate the effects of evaporator geometry on drying time and energy consumption. The model was validated using experimental data available in the literature. The effects of the evaporator's geometrical specifications on heat and mass transfer and pressure drops on both sides of the evaporator were investigated. Then, the energy consumption and drying time of the dryer were determined. The results indicated that the energy consumption is reduced by 12% when the number of rows in the evaporator is increased from 2 to 4. Increasing the number of columns from 2 to 4 could reduce energy consumption by 8%. The energy consumption increases by 18% when the outer diameter of the tube is increased from 6 mm to 10 mm. Increasing the longitudinal tube pitch from 10 mm to 30 mm leads to a 21% increase in energy consumption. (C) 2015 Elsevier Ltd and IIR. All rights reserved.
Keywords: Evaporator; Heat pump tumble dryer; Modeling; Energy consumption; FRICTION CHARACTERISTICS; AIRSIDE PERFORMANCE; CARBON-DIOXIDE; EXCHANGERS; DRYER; CO2; SIMULATION; FLUID; MASS; Thermodynamics; Engineering